Divergent estimates of herd‐wide caribou calf survival: Ecological factors and methodological biases. Issue 15 (21st July 2020) - Ellington, E. Hance; Lewis, Keith P.; Koen, Erin L.; Vander Wal, Eric
Abstract: Population monitoring is a critical part of effective wildlife management, but methods are prone to biases that can hinder our ability to accurately track changes in populations through time. Calf survival plays an important role in ungulate population dynamics and can be monitored using telemetry and herd composition surveys. These methods, however, are susceptible to unrepresentative sampling and violations of the assumption of equal detectability, respectively. Here, we capitalized on 55 herd‐wide estimates of woodland caribou ( Rangifer tarandus caribou ) calf survival in Newfoundland, Canada, using telemetry ( n  = 1, 175 calves) and 249 herd‐wide estimates of calf:cow ratios (C:C) using herd composition surveys to investigate these potential biases. These data included 17 herd‐wide estimates replicated from both methods concurrently ( n  = 448 calves and n  = 17 surveys) which we used to understand which processes and sampling biases contributed to disagreement between estimates of herd‐wide calf survival. We used Cox proportional hazards models to determine whether estimates of calf mortality risk were biased by the date a calf was collared. We also used linear mixed‐effects models to determine whether estimates of C:C ratios were biased by survey date and herd size. We found that calves collared later in the calving season had a higher mortality risk and that C:C tended to be higher for surveys conducted later in the autumn. When we used these relationships to modify estimates of herd‐wide calf survival derived from telemetry and herd composition surveys concurrently, we found that formerly disparate estimates of woodland caribou calf survival now overlapped (within a 95% confidence interval) in a majority of cases. Our case study highlights the potential of under‐appreciated biases to impact our understanding of population dynamics and suggests ways that managers can limit the influence of these biases in the two widely applied methods for estimating herd‐wide survival. Abstract : We investigated whether estimates of calf mortality risk and calf:cow ratios were biased by unrepresentative sampling and violations of equal detectability, respectively, using 35 years of caribou monitoring data. We found that caribou calves collared later in the calving season had a higher mortality risk and caribou calf:cow ratios were higher when surveys were conducted later in the autumn. If these biases go undetected, they could impact management.